Female Existentialism in Monkey Grip by Helen Garner - Arafah, Burhanuddin; Asri, Delukman; Hanafiah, Waode; Ruslin; Ilmi, Nur; Pratiwi, Alifiah; Astiantih, Susi (Journal of language teaching and research, 2024)
This study aimed to analyze female existentialism in Helen Garner's "Monkey Grip" using a descriptive qualitative method. In this context, the data obtained were carefully reviewed, presented, and analyzed through stylistic analysis. The results showed that female existentialism was expressed in two patterns. Firstly, the female speech was similar to the male, accompanied by the open expression of sexual desires and male circle words. Secondly, female actions contained the feminine movement to overcome discrimination problems and interact with many males. The results showed that the female character was considered a feminist representative against male stereotypes.